The Venues of Recreation in a Former Socialist Town - Ispán, Ágota Lídia (Ethnographica et Folkloristica Carpathica, 2022)
In Hungary 10–14 towns were classified as socialist towns. In 1953 the construction of the would-be Leninváros (present day Tiszaújváros) was started.  The town planners laid stress on building facilities for the relaxation and recreation of people and parks, playgrounds, beaches and holiday homes were available for everyone. However, the public places designated as recreational facilities for the inhabitants of the town, which was intended to be an idealistic one, did not satisfy their needs. They preferred to spend their free time in their ‘household plots’ in town. Small gardens and garages complemented a lot of apartments in panel blocks, thus increasing the available living space in a special manner. These “private properties” mostly had the function whose mass demand was unexpected for the planners of the city. The author describes how they helped residents, who often had a village background, making the socialist type of town more liveable.